Hypothalamic-Pituitary-Adrenal Axis Relation with Employees in Samarra University - Ameerah Abdulmunem Yassen (American Journal of Biology and Natural Sciences, 2026)
Background: Workplace stress activates the hypothalamicpituitary-adrenal (HPA) axis and can lead to cortisol dysregulation, measurable through serum biomarkers. Aim of the study: The purpose of this study was to explore the relationship between type of job (technicians , teachers and administrators) with brain and its effect on neurotransmitter. Methods: This study was conducted on 90 Samarra University employees during the period from October 2023 to January 2024. Biochemical parameters included estimating the activity of cortisol, Beta Nerve Growth Factor (β-NGF), serotonin, melatonin, and dopamine. Result: The levels of cortisol significantly increase in teachers (174.09 ± 23.76 ng/mL) compared to administrators and technicians (p = 0.009). β-NGF, Serotonin, and Melatonin levels showed no significant differences between the groups (p >0.05). Dopamine shows a significant increase in teachers compared to administrators and technicians (p = 0.03). conclusion: The present study concluded that the type of work associated with the psychological and physical stress affect certain hormones and neurotransmitters, as well as some cellular and enzymatic stress markers.